2013
DOI: 10.1371/journal.pone.0066567
|View full text |Cite
|
Sign up to set email alerts
|

Features of Variable Number of Tandem Repeats in Yersinia pestis and the Development of a Hierarchical Genotyping Scheme

Abstract: BackgroundVariable number of tandem repeats (VNTRs) that are widely distributed in the genome of Yersinia pestis proved to be useful markers for the genotyping and source-tracing of this notorious pathogen. In this study, we probed into the features of VNTRs in the Y. pestis genome and developed a simple hierarchical genotyping system based on optimized VNTR loci.Methodology/Principal FindingsCapillary electrophoresis was used in this study for multi-locus VNTR analysis (MLVA) in 956 Y. pestis strains. The gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 39 publications
0
32
0
2
Order By: Relevance
“…The MLtree of 78 Guertu isolates and 368 public Y. pestis strains indicated that all Guertu isolates belong to a same phylogroup, 0.ANT1 ( Supplementary Fig. 3), which is only distributed in the Guertu region according to previous studies 44,54 .…”
Section: Methodsmentioning
confidence: 81%
“…The MLtree of 78 Guertu isolates and 368 public Y. pestis strains indicated that all Guertu isolates belong to a same phylogroup, 0.ANT1 ( Supplementary Fig. 3), which is only distributed in the Guertu region according to previous studies 44,54 .…”
Section: Methodsmentioning
confidence: 81%
“…The repeat numbers for 25 VNTR loci in 97 Y. pestis strains representing the genetic diversity of the whole species, four Yersinia pseudotuberculosis strains, 15 and 38 Y. pestis strains from FSU plague foci 14 were obtained from previously published articles (Supplemental Table 1). The VNTR diversity information for these strains was obtained from the MLVA bank for Microbes Genotyping database (http://microbesgenotyping.…”
Section: Methodsmentioning
confidence: 99%
“…13 Understanding the phenotypic features and genetic diversity of Y. pestis isolates is important in characterizing a plague focus and contributes to the prevention and control of plague. Molecular genotyping and evolutionary analyses were used to describe the phylogenetic positions of the Junggar strains, including a multiple-locus variable number of tandem repeats analysis (MLVA), which is based on the diversity of variable numbers of tandem repeats (VNTR), 14,15 typing with clustered regularly interspaced short palindromic repeats (CRISPR), which is based on the varying compositions of the spacer arrays in three CRISPR loci in the genome, 16 and whole-genome single-nucleotide polymorphism (SNP) analysis. 17 However, only 1-3 Junggar strains were used in those studies, so the fully representative genetic diversity of the Y. pestis population in Junggar Basin focus was not determined.…”
Section: Introductionmentioning
confidence: 99%
“…To establish a genotyping system for tracing the source of this notorious pathogen, Li et al [25] studied the traits of VNTRs in the Y. pestis genome and established a simple hierarchical genotyping system based on MLVA-CE analysis. Their results demonstrate that the MLVA-CE genotyping method improves the study of Y. pestis with respect to source tracing and microevolution of this pathogen, which compares favorably with single nucleotide polymorphismbased phylogenic analysis, but costs less time and money.…”
Section: Detecting and Diagnosing Bacteriamentioning
confidence: 99%